INTERIOR DESAIN UNTUK MENINGKATKAN KENYAMANAN DAN AKSESIBILITAS PADA PENATAAN RUANG PERPUSTAKAAN KOTA BOGOR - Dewi Astuti; Rakhmanita, Rakhmanita; Sumaiyah Fitrian Dini (Asosiasi Dosen Muda Indonesia, 2025)
The Bogor City Library plays an important role in creating a strong literacy ecosystem, functioning as a center for community empowerment by providing access to information and skills development. This research aims to analyze circulation patterns and spatial planning in libraries, in order to increase public interest in utilizing existing facilities. Although founded in 1972, the library faced serious challenges, including inadequate space and unattractive facilities, such as a non-functioning multimedia room and a lack of private rooms for discussions. The low literacy rate in Bogor City shows the need for more efforts to increase interest in reading. It is hoped that the